Determination of Radiation Shielding Features of Polyvinyl Alcohol/Magnetite-Bismuth Oxide Composite Using Precise Computational Methods and Monte Carlo Code - Fariba Baroonzadeh; Maziyar Mahdavi; Mohammad Hosseini; Reza Jalli (Iranian Journal of Medical Physics)
Introduction: Bismuth efficiency in shielding superficial tissues in computed tomography (CT) scans has been challenged due to the imbalance between image quality and dose reduction. The aim of this study is to reduce bismuth in shields and investigate the possibility of substitution with lower atomic materials. Material and Methods: Five different compounds, including raw polyvinyl alcohol (PVA) and four other samples containing variable weight fractions of bismuth oxide and with a constant fraction of magnetite were selected. Shielding factors, including linear attenuation coefficient(μ), mass attenuation coefficient(μρ), half-value layer (HVL), electron density (Ne), and effective atomic number (Zeff), were evaluated over a wide range of energy by precise computational methods, XCOM, and Monte Carlo N-Particle code. Results: Increasing the bismuth oxide concentration improves the radiation attenuation and absorption process. This effect was observed in the μρ graphs to medium energies (E < 0.3560 MeV).The simultaneous evaluation of Ne and Zeff predicts increased absorption due to the increased and dominant photoelectric effect (<0.1000 MeV), the raised Compton effect (0.1000 < E < 0.3560 MeV; followed by scattering owing to the predominant Compton effect), and formation (E ≈ 1.2200 MeV)and dominance of pair production phenomenon (E > 3.0000 MeV).Also, a quantitative analysis of absorption through HVL in several used energies showed the efficacy of these compounds in ionizing radiation absorption. Conclusion: This study establishes the advantages of substituting bismuth with compounds having lower atomic number materials, and the possibility of alleviating bismuth and replacing it with magnetite and PVA in designing radiation shields in CT scans has been confirmed.